2023
DOI: 10.1111/ctr.14956
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, mortality, and risk factors associated with carbapenem‐resistant Acinetobacter baumannii bacteremia within 30 days after liver transplantation

Abstract: Carbapenem‐resistant Acinetobacter baumannii bacteremia (CRAB‐B) is a fatal infectious complication of liver transplantation (LT). This study investigated the incidence, effects, and risk factors associated with CRAB‐B during the early post‐LT period. Among 1051 eligible LT recipients, 29 patients experienced CRAB‐B within 30 days of LT with a cumulative incidence of 2.7%. In the patients with CRAB‐B (n = 29) and matched controls (n = 145) by nested‐case control design, the cumulative incidence of death on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…CRAB is extremely difficult to eradicate from healthcare facilities, frequently causing nosocomial outbreaks [ 44 , 60 , 61 , 62 ]. For this reason, its epidemiology deeply varied not only between different geographical regions, but also among hospitals in the same areas and wards in the same hospital.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CRAB is extremely difficult to eradicate from healthcare facilities, frequently causing nosocomial outbreaks [ 44 , 60 , 61 , 62 ]. For this reason, its epidemiology deeply varied not only between different geographical regions, but also among hospitals in the same areas and wards in the same hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Shi et al [ 57 ] reported that 62% of the A. baumannii isolated from blood cultures in their cohort was MDR. Therefore, post-LT CRAB infections have high mortality rates of 50–65% [ 44 , 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within these limits, crude mortality due to MDRO BSI ranged from 15.4% (VRE 30-day mortality in liver transplant recipients) (20) to 82.4% (CRE mortality in liver transplant recipients admitted to intensive care) (21). Excluding patients in the intensive care setting, crude mortality remained as high as 65.5% (CRAB 10-and 30-day mortality in liver transplant recipients) (22). Where mortality due to MDRO BSI was assessed alongside drugsusceptible BSI, MDRO BSIs were consistently associated with a higher mortality rate irrespective of MDRO or transplant type (Table 2).…”
Section: Pooled Estimates Of Mdro Bsis In Sot Recipientsmentioning
confidence: 99%
“…Up to one-third of bacteremic Acinetobacter baumannii infections (ABI) patients progress to septic shock, associated with a high mortality rate of 20–60% of cases [19–23,24 ▪ ].…”
Section: Introductionmentioning
confidence: 99%